Exercise # 2.3: Reduce Each of The Following Matrices To The Indicated Form
Exercise # 2.3: Reduce Each of The Following Matrices To The Indicated Form
Exercise # 2.3: Reduce Each of The Following Matrices To The Indicated Form
3
Question # 1 1 3 1
R 0 5 6
Reduce each of the following matrices
to the indicated form.
0 0 8
1 3 1
(i) 2 1 4 Echelon form 1
1 3
3 4 5 R2
R 0 1
6 5
Solution: 5 R 3
0 0 1 8
1 3 1
2 1 4
3 4 5 Which is Echelon form
1 3 1 2 3 1 9
R 2 (2R1 ) 1 1 Reduced Echelon form
R 2 2 1 6 4 2
2 3
R (3R1 )
3
3 3 4 9 5 3 3 1 3 2
Solution:
1 3 1
2 1 9
R 0 5 6
3
1 1 3
2
0 5 2 3 1 3 2
1 1 2 3
1 3 1 R 2 3 1 9 R 1 R 2
R 0 5 6 R 2 R 3 3 1 3 2
0 5 5 2 6
1 1 2 3 1 0 1 0
R 2 ( 2R1 )
R 2 2 3 2 1 4 9 6 R 0 1 1 3
R (3R1 )
3
3 3 1 3 36 2 9 0 0 1 1
1 1 2 3 1 0 0 0 1 1 0 1
R1 R 3
R 0 5 5 15 R 0 0 1 0 1 1 3 1
R R3
2
0 4 3 11 0 0 1 1
1 1 2 3 1 0 0 1
R 0 1 1 3 2
R 0 1 0 2
R
5
0 4 3 11 0 0 1 1
1 1 2 1 0 3
R 0 5 3 R 0 1 1
0 3 1 0 0 4
1 1 2 1 0 3
R 0 5 6 3 2 R 2 ( 2R 3 )
R 0 1 1
R3
4
0 3 1 0 0 1
1 1 2 1 0 0
R 2 R3
R 0 1 1
R 0 0 1 0 1 1
R ( 3R 3 )
1
0 3 1 0 0 1
1 1 2 1 0 0
R 0 1 1 R 3 3R 2 R 0 1 0
0 3 3 1 3 0 0 1
1 0 2
2 1 1
3 0 3
1 0 2
R 2 (2R1 )
R 2 2 1 0 1 4
R (3R1 )
3
3 3 0 0 3 6
1 0 2
R 0 1 5
0 2 9
1 0 2
0 1 5 R 3 ( 2R 2 )
0 2 2 9 10
1 0 2
0 1 5
0 0 1
1 0 2
0 1 5
R3
1
0 0 1
Find the inverse of the following matrices by using elementary Row or Column
operation.
(i)
4 2 5
A2 1 0
1 2 3
4 2 5 1 0 0
R 2 1 0 0 1 0
1 2 3 0 0 1
1 2 3 0 1 0
R 2 1 0 1 0 0 R 1 R 3
4 2 5 0 0 1
1 2 3 0 0 1
R 2 2R 1
R 2 2 1 4 0 6 0 0 1 0 0 2
R 3 4R 1
4 4 2 8 5 7 1 0 0 0 0 4
1 2 3 0 0 1
R 0 1 11 0 1 2
0 6 17 1 0 4
1 2 3 0 1
0
R 0 5 6 6 17 0 1 1 0 2 4 R2 R3
0 6 17 1 0 4
1 2 3 0 1
0
R 0 1 11 1 1 2 R2 R3
0 6 17 1 0 4
1 2 3 0 1
0
R 0 1 11 1 1 2 R3 6R2
0 0 49 5 6 8
1 2 3 0 0 1
R3
R 0 1 11 1 1 2
49
5 6 8
0 0 1 49 49 49
15 18 25
1 2 0 49 49 49
R 0 1 11 1 1 2 R1 3R3
5 6 8
0 0 1
49 49 49
15 18 25
1 2 0 49 49 49
6 17 10
R 0 1 0 R1 11R3
49 49 49
5 6 8
0 0 1
49 49 49
3 16 5
1 0 0 49 49 49
6 17 10
R 0 1 0 R1 2R2
49 49 49
5 6 8
0 0 1
49 49 49
3 16 5
49 49 49
6 17 10
Hence A 1
49 49 49
5 6 8
49 49 49
(ii)
3 1 6
A 1 3 4
1 5 1
3 1 6 1 0 0
1 3 4 0 1 0
1 5 1 0 0 1
1 3 4 0 1 0
R 3 1 6 1 0 0 R1 R 2
1 5 1 0 0 1
1 3 4 0 10
R 2 (3R1 )
R 3 3 1 9 6 12 1 0 0 3 0 0
R 3 R1
1 1 5 3 1 4 0 0 0 1 1 0
1 3 4 0 1 0
R 0 10 6 1 3 0
0 8 5 0 1 1
1 3 4 0 1 0
R 0 10 8 6 5 1 0 3 1 0 1 R 2 R3
0 8 5 0 1 1
1 3 4 0 1 0
R 0 2 1 1 2 1
0 8 5 0 1 1
1 3 4 0 1 0
R 0 2 1 1 2 1 R3 4 R2
0 0 8 8 5 4 0 4 1 8 1 4
1 3 4 0 10
R 0 2 1 1 2 1 R3 (8 R1 )
0 0 1 4 7 5
1 0 3 0 4 4 0 16 1 28 0 20
R2 R3
R 0 0 2 0 1 1 1 4 2 7 1 5
R1 (4 R3 )
0 0 1 4 7 5
1 3 0 16 29 20
R 0 2 0 5 9 6
0 0 1 4 7 5
1 3 0 16 29 20
2 9
R 0
5 6 R2
0
2 2 2 2 2
0 0 1 4 7 5
1 3 0 16 29 20
R 0 1 0 3
5 9
2 2
0 0 1 4 7 5
15 18
1 0 3 3 0 0 16
2
29
2
20 9
5 9
R 0 1 0 3 R1 (3R2 )
2 2
0 0 1 4 7 5
17 31
1 0 0 11
2 2
5 9
R 0 1 0 3
2 2
0 0 1 4 7 5
17 31
2 11
2
1 5 9
Hence A 3
2 2
4 7 5
(iii)
1 2 3
0 2 0
2 2 2
1 2 3 1 0
0
R 0 2 0 0 1 0 R3 2 R1
2 2 2 4 26 0 2 0 0 1 0
1 2 3 1 0 0
R 0 2 0 0 1 0
0 2 4 2 0 1
1 0 2 2 3 0 1 0 0 1 0 0
R1 R2
R 0 2 0 0 1 0
R3 R2
0 0 22 04 2 0 0 1 1 0
1 0 3 1 1 0
R 0 2 0 0 1 0
0 0 4 2 1 1
1 0 3 1 1 0
R2
2
0 2
1
R 0 0 0
2 2 R3
4 2 1 1 4
0 0
4 4 4 4
1 0 3 1 1 0
1
R 0 1 0 0 0
2
1 1 1
0 0 1
2 4 4
3 3 3
1 0 3 3 1 1 0
2 4 4
1
R 0 1 0 0 0 R1 3R3
2
1 1 1
0 0 1
2 4 4
1 1 3
1 0 0
2 4 4
1
R 0 1 0 0 0
2
1 1 1
0 0 1
2 4 4
1 1 3
2 4 4
1
1
Hence A 0 0
2
1 1 1
2 4 4
(iv)
1 2 1
0 1 3
1 0 2
1 2 1 1 0 0
R 0 1 3 0 1 0
1 0 2 0 0 1
1 2 1 1 0 0
R 0 1 3 0 1 0 R3 R1
0 2 3 1 0 1
1 2 1 1 0 0
R 0 1 3 0 1 0 2
R
1
0 2 3 1 0 1
1 0 5 1 0 2
R1 (2 R2 )
R 0 1 3 0 1 0
R 2 R2
3
0 0 3 1 2 1
1 0 5 1 0
2
R
R 0 1 3 0 1 0 2
3
1 2 1
0 0 1
3 3 3
2 4 5
1 0 0
3 3 3
R ( 5 R )
R 0 1 0 1
1 3
1 1
R2 3R3
1 2 1
0 0 1
3 3 3
2 4 5
3
3 3
1
Hence A 1 1 1
1 2 1
3 3 3
Question # 3
1 0 2
2 2 1
(i) 1 2 3
Solution
1 0 2
Let A 2 2 1
1 2 3
1 0 2
R2 (2 R1 )
R 0 2 5
R3 R1
0 2 1
1 0 2
R 0 2 5 R3 R2
0 0 4
1 0 2
R2
R 0 1
5 2
2 R3
0 0 1 4
Rank of 𝐴 = 3
(ii)
3 1 4
0 2 1
1 1 2
Solution:
3 1 4
Let A 0 2 1
1 1 2
1 1 2
R 0 2 1 R1 R3
3 1 4
1 1 2
R 0 2 1 R1 (3R3 )
0 4 2
1 1 2
R 0 2 1 R3 (2 R2 )
0 0 0
Rank of 𝐴 = 2
Question # 4
2 3 4 5
3 4 5 6
(i) 4 4 matrix
4 5 6 7
9 10 11 12
Solution:
2 3 4 5
3 4 5 6
Let A =
4 5 6 7
9 10 11 12
2 3 4 5
1 1 1 1 R R
2 1
R
1 1 1 1 R3 R2
9 10 11 12
1 1 1 1
2 3 4 5
R R1 R2
1 1 1 1
9 10 11 12
1 1 1 1
R2 (2 R1 )
0 1 2 3
R R3 R1
0 0 0 0
R (9 R )
4 1
0 1 2 3
1 1 1 1
R2 (2 R1 )
0 1 2 3
R R3 R1
0 0 0 0
R (9 R )
4 1
0 1 2 3
1 1 1 1
0 1 2 3
R R4 R2
0 0 0 0
0 0 0 0
Rank of A = 2
𝐄𝐱𝐞𝐫𝐜𝐢𝐬𝐞 𝟐. 𝟒
Question # 1 4 3 1
Solve the following system of equation by
A 2 1 4
matrix in version method.
(i) 4𝑥 − 3𝑦 + 𝑧 = 11 1 2 2
2𝑥 + 𝑦 − 4𝑧 = −1 1 −4 2 −4 2 1
𝐴 =4 +3 +1
2 −2 1 −2 1 2
1 ⋅ 𝑥 + 2𝑦 − 2𝑧 = 1
= 4 −2 + 8 + 3 −4 + 4 + 1 4 − 1
Solution:
= 24 + 3
𝐌𝐚𝐭𝐫𝐢𝐱 𝐟𝐨𝐫𝐦
= 27
4 3 1 x 1
Now we find all cofactors
2 1 4 y 1
1 −4
𝐴11 = (−1)1+1 = +1 (−2 + 8) = 6
2 −2
1 2 2 z 1
2 −4
𝐴12 = (−1)1+2 = −1 −4 + 4 = 0
1 −2
𝐴𝑋 = 𝐵 ⇒ 𝑋 = A−1 𝐵 → (i)
2 1
𝐴13 = (−1)1+3 = +1 (4 − 1) = 3
1 2
Here
−3 1
𝐴21 = (−1)2+1 = −1(6 − 2) = −4
4 3 1 x 11 2 −2
4 1
A 2 1 4 , X y , B 1
𝐴22 = (−1)2+2
1 −2
= +1(−8 − 1) = −9
1 2 2 z 1 1 −2
𝐴23 = (−1)2+3 = −1 −3 + 8 = −5
4 −3
4 3 1 −3 1
𝐴31 = (−1)3+1 = +1(12 − 1) = 11
1 −4
A 2 1 4 4 1
𝐴32 = (−1)3+2 = −1(−16 − 2) = 18
2 −4
1 2 2
4 −3
𝐴33 = (−1)3+3 = +1(4 + 6) = 10
2 1
t 66 4 11
A11 A12 A13 1
0 9 18
27
Adj A A21 A22 A23 33 11 10
A32 A32 A31 81
1
t x 27
6 0 3 27
54
4 9 11
81
11 18 10 27
27
6 4 11
37
54
0 9 18
27
3 11 10
x 3
A1
1
Adj A y 1
A
z 2
6 4 11
1 ⇒ 𝑥 = 3, 𝑦 = 1, 𝑧 = 2
0 9 18
27
(ii)
3 11 10
𝑥+𝑦+𝑧 =1
−1
Put value of 𝐴 & B in eq (i)
𝑥 + 𝑦 − 2𝑧 = 3
2𝑥 + 𝑦 + 𝑧 = 2
So eq (i) becomes
𝑋 = A−1 𝐵 Solution:
6 4 11 11 1 1 1 x 1
1 1 1 2 y 3
0 9 18 1
27
3 11 10 1 2 1 1 z 2
1 1
𝐴23 = (−1)2+3 = −1 1 − 2 = 1
2 1
1 1
𝐴31 = (−1)3+1 = +1 −2 − 1 = −3
1 −2
𝐴𝑋 = 𝐵 ⇒ 𝑋 = A−1 𝐵 → (i)
1 1
𝐴32 = (−1)3+2 = −1 −2 − 1 = 3
1 −2
Here
1 1
𝐴33 = (−1)3+3 = +1 1 − 1 = 0
1 1 1 x 1 1 1
A 1 1 2 , X y , B 3
t
2 1 1 z 2 A11 A12 A13
1 1 1 Adj A A21 A22 A23
A 1 1 2 A32 A32 A31
t
2 1 1 3 5 1
=1
1 −2
−1
1 −2
+1
1 1 Adj A 0 1 1
1 1 2 1 2 1
=∣ 1 + 2 − 1 1 + 4 + 1 1 − 2 3 3 0
=3−5−1 3 0 3
= −3
Adj A 5 1 3
Now we find all cofactors
1 1 0
1 −2
𝐴11 = (−1)1+1 = +1 (1 + 2) = 3
1 1 1
A1 Adj A
1 −2 A
𝐴12 = (−1)1+2 = −1 1 + 4 = −5
2 1
3 0 3
1 1
𝐴13 = (−1)1+3 = +1(1 − 2) = −1
2 1
5 1 3
1
1 1 3
𝐴21 = (−1)2+1 = −1(1 − 1) = 0
1 1 1 1 0
1 1
𝐴22 = (−1)2+2 = +1(1 − 2) = −1 Put value of 𝐴−1 & B in eq (i)
2 1
𝑋 = A−1 𝐵
3 0 3 1 Question # 2
5 1 3 3
1 Solve the following system of
3 equations by the Gauss elimination
1 1 0 2 and Gauss-Jordan method.
𝑥 − 𝑦 + 4𝑥 = 4
306 2𝑥 + 2𝑦 − 𝑧 = 2
3𝑥 − 2𝑦 + 3𝑧 = −3
5 3 6
1
3
Solution:
1 3 0
Matrix form
3
1 1 4 x 4
1 2 2 1 y 2
2
3 3 2 3 z 3
2
3
3 Augmented matrix
2 1 1 4 4
3
[A/B] 2 2 1 2
2
3 3 2 3 3
1 1 4 4
x 1
R2 (2 R1 )
y 2 R 2 2 2 2 1 8 2 8
3 R (3R1 )
2 3
z 3 3 2 3 3 12 3 12
3
1 1 4 4
2 2
𝑥 = 1, 𝑦 = , 𝑧 = −
3 3 R 0 4 9 6
0 1 9 15
1 1 4 4 𝑦 − 9 2 = −15
R 0 1 9 15 R2 R3 𝑦 = −15 + 18 = 3
𝑦=3
0 4 9 6
From 𝑅1 , we have
1 1 4 4
1. 𝑥 − 1 ⋅ 𝑦 + 4𝑧 = 4
R 0 1 9 15 R 2 R 3 Put value of y, z we have
0 4 9 6 𝑥−3+4 2 =4
1 1 4 4 𝑥−3+8=4
𝑥 = −1
R 0 1 9 15 R 3 ( 4R 2 )
(b)
0 0 4 4 9 36 6 60
For Gauss-Jordon elimination method.
1 1 4 4
Consider the Echelon form
R 0 1 9 15 1 1 4 4
0 0 27 54 0 1 9 15
1 1 4 4 0 0 1 2
R 0 1 9 15 3
R
1 0 1 1 49 4 15
27
0 0 1 2 R 0 1 9 15 R 1 R 2
It is Gauss Elimination form (Echelon form). 0 0 1 2
From 𝑅3 , we have
1 0 5 11
0⋅𝑥+0⋅𝑦+1⋅𝑧 =2
R 0 1 9 15
𝑧=2
0 0 1 2
From 𝑅2 , we have
0 ⋅ 𝑥 + 𝑦 − 9𝑧 = −15
1 0 0 1 1 2 2 2
R 0 1 0 3 R 2 4 1 0 R1 ↔ R 2
0 0 1 5 8 3 2
2
2𝑥 + 4𝑦 − 𝑧 = 0 1 2 2 2
𝑥 − 2𝑦 − 2𝑧 = 2
R 0 1
3 1 R2
8 2 8
−5𝑥 − 8𝑦 + 3𝑧 = −2
0 18 7 8
Solution:
1 2 2 2
Matrix form
3 1
2 4 1 x 0 R 0 1 R 3 18R 2
8 2
1 2 2 y 2 27
0 18 18 7 8 9
4
5 8 3 z 2
Augmented Matrix
1 2 2 From 𝑅1 , we have
2
3 1 1 ⋅ 𝑥 − 2𝑦 − 2𝑧 = 2
R 0 1
8 2 Put value of y , z, we have
1
0 0 1
4 𝑥 − 2 −2 − 2 4 = 2
1 2 2 2 𝑥+4−8=2
𝑥−4=2
R 0 1
3 1
4R 3
8 2
𝑥=6
0 0 1 4
(b)
3 1 3
0⋅𝑥+1⋅𝑦+ 𝑧 =−
8 2 1 2 2 2 4 2 1
3 1
Put value of y R 0 1 R1 2R2
8 2
3 1
𝑦+ 4 =− 0 0 1 4
8 2
3 1 5
𝑦+ =− 1 0 1
2 2 4
1
1 3 R 0 1
3
𝑦=− − 8 2
2 2
−1 − 3 0 0 1 4
y=
2
4
𝑦=−
2
𝑦 = −2
5 5 1 2 0 x 4
1 0 1 5
4 4 3
R2 R3 3 1 0 y 5
R 0 1
3 3
1 3
8
8 8 2 2 5
R1 R3 2 0 1 z 1
0 0 1 4 4
𝐴𝑋 = 𝐵
1 0 0 6
R 0 1 0 2
Here
1 2 0 x 4
0 0 1 4
A 3 1 0 , X y & B 5
It is Gauss-Jordon elimination form (Reduced
Echelon form). 2 0 1 z 1
Here we have the solution
1 −2 0
𝑥=6
𝐴 = 3 1 0
𝑦 = −2 2 0 1
1 0 3 0
𝑧=4 =1 +2 +0
0 1 2 1
Question # 3 = 1 1−0 +2 3−0
Use Cramer’s Rule to solve the following =1+6
system of equations. 𝐴 =7
(i) −4 −2 0
Solution: 𝐴1 = −5 1 0
−1 0 1
𝑥 − 2𝑦 = −4 ⇒ 𝑥 − 2𝑦 + 0 ⋅ 𝑧 = −4
1 0 −5 0
3𝑥 + 𝑦 = −5 ⇒ 3𝑥 + 𝑦 + 0 ⋅ 𝑧 = −5 = −4 +2 +0
0 1 −1 1
2𝑥 + 𝑧 = −1 ⇒ 2𝑥 + 0𝑦 + 𝑧 = −1 = −4 1 − 0 + 2 −5 + 0
Matrix form = −4 + 10
=6
1 −4 0 3𝑥 + 𝑦 + 𝑧 = 7
𝐴2 = 3 −5 0
2 −1 1 Matrix Form
−5 0 3 0
=1 +4 +0 1 1 2 x 10
−1 1 2 1
= 1 −5 + 0 + 4 3 − 0 2 1 2 y 4
= −5 + 12
3 1 1 z 7
=7
𝐴𝑋 = 𝐵
1 −2 −4
𝐴3 = 3 1 −5
2 0 −1 Here
1 −5 3 −5 3 1
=1 +2 −4 1 1 2 x 10
0 −1 2 −1 2 0
= 1 −1 + 0 + 2 −3 + 10 − 4(0 − 2) A 2 1 2 , X y & B 4
= 1 −1 + 2 7 − 4 −2
3 1 1 z 7
= −1 + 14 + 8
= 21 1 −1 2
𝐴 = 2 1 −2
So solution is 3 1 1
𝐴1 −14
𝑥= = = −2
𝐴 7 1 −2 2 −2 2 1
=1 +1 +2
1 1 3 1 3 1
𝐴2 7
𝑦= = =1
𝐴 7 = 1 1+2 +1 2+6 +2 2−3
𝐴3 21
𝑦= = =3 =3+8−2=9
𝐴 7
|𝐴| = 9
(ii)
10 −1 2
𝐒𝐨𝐥𝐮𝐭𝐢𝐨𝐧: 𝐴1 = −4 1 −2
7 1 1
𝑥 − 𝑦 + 2𝑧 = 10
1 −2 −4 −2 −4 1
= 10 +1 +2
2𝑥 + 𝑦 − 2𝑧 = −4 1 1 7 1 7 1
= 10 1 + 2 + 1 −4 + 14 + 2(−4 − 7)
= 10 3 + 1 10 + 2(−11) Question # 4
= 30 + 10 − 22
Solve the following system of homogenous
= 18
equation.
1 10 2
𝐴2 = 2 −4 −2
3 7 1 (i)
−4 −2 2 −2 2 −4
=1 − 10 +2
7 1 3 1 3 7 𝑥1 − 𝑥2 + 𝑥3 = 0
= 1 −4 + 14 − 10 2 + 6 + 2(14 + 12)
𝑥1 + 2𝑥2 − 𝑥3 = 0
= 10 − 10 8 + 2(26)
= 10 − 80 + 52 2𝑥1 + 𝑥2 + 3𝑥3 = 0
= −18
Solution:
1 −1 10
𝐴3 = 2 1 −4
3 1 7 1 1 1
1 −4 2 −4 2 1
=1
1 7
+1
3 7
+ 10
3 4 Here A 1 2 1
= 1 7 + 4 + 1 14 + 12 + 10(2 − 3) 2 1 3
= 11 + 26 − 10
We check
= 27
1 −1 1
So solution is
𝐴 = 1 2 −1
𝐴1 18 2 1 3
𝑥= = =2
𝐴 9 2 −1 1 −1 1 2
=1 +1 +1
𝐴2 −18 1 3 2 3 2 1
𝑦= = = −2
𝐴 9 = 1 6 + 1 + 1 3 + 2 + 1(1 − 4)
𝐴3 27
𝑦= = =3 = 1 7 + 5 + 1 −3
𝐴 9
=7+5−3
𝐴 =9 So system has non-trivial solution.
(ii) 2 x1 x2 x3 0
𝑥1 + 𝑥2 + 2𝑥3 =0
−2𝑥1 + 𝑥2 − 𝑥3 =0 3 x2 3 x3 0
−𝑥1 + 5𝑥2 + 4𝑥3 =0
3𝑥2 = −3𝑥3
Solution:
𝑥2 = −𝑥3 → (𝐴)
1 1 2
Put value of 𝑥2 in eq (i)
Here A 2 1 1
𝑥1 − 𝑥3 + 2𝑥3 = 0
1 5 4
𝑥1 + 𝑥3 = 0
1 1 2 𝑥1 = −𝑥3 → (𝐵)
𝐴 = −2 1 −1
−1 5 4 Put value of 𝑥1 , 𝑥2 in eq (iii)
𝐵 ⇒ 𝑥1 = −𝑡
Which is non-trivial solution. 1 1 2 0
ALTERNATE METHOD 2 1 1 0
𝑥1 + 𝑥2 + 2𝑥3 =0
1 5 4 0
−2𝑥1 + 𝑥2 − 𝑥3 =0
−𝑥1 + 5𝑥2 + 4𝑥3 =0
1 1 2 0
R 2 2 R1
R 2 2 1 2 1 4 0
Solution:
R R1
1 1 2 3
1 1 5 1 4 2 0
Here A 2 1 1
1 1 2 0
1 5 4
R 0 3 3 0
1 1 2
𝐴 = −2 1 −1 0 6 6 0
−1 5 4
1 −1 −2 −1 −2 1 1 1 2 0
𝐴 =1 −1 +2
5 4 −1 4 −1 5
R 0 3 3 0 R3 (2 R2 )
𝐴 = 1 4 + 5 − 1 −8 + 1 + 2 −18 + 1
0 0 0 0
𝐴 = 9 + 9 − 18
𝐴 =0 1 1 2 0
R 0 1 1 0 2
So system has non-trivial solution. R
3
𝑥1 + 𝑥2 + 2𝑥3 = 0 → (i) 0 0 0 0
−2𝑥1 + 𝑥2 − 𝑥3 = 0 → (ii)
−𝑥1 + 5𝑥2 + 4𝑥3 = 0 → (iii)
From 𝑅2 , we have
Here the augmented matrix
0𝑥1 + 𝑥2 + 𝑥3 = 0
⇒ 𝑥2 + 𝑥3 = 0 → (𝐴)
From 𝑅1 , we have 1 5 3
Here A 5 1
1. 𝑥1 + 1. 𝑥2 + 2𝑥3 = 0
1 2
𝑥1 + 𝑥2 + 2𝑥3 = 0 → (𝐵)
It is given that the system has non-trivial
solution, so we put
Let 𝑥3 = 𝑡
A 0
(A) ⇒ 𝑥2 + 𝑡 = 0
1 5 3
5 1 −𝜆 = 0
⇒ 𝑥2 = −𝑡 1 2 𝜆
B ⇒ 𝑥1 + −𝑡 + 2𝑡 = 0 1 −𝜆 5 −𝜆 5 1
1 −5 +3 =0
2 𝜆 1 𝜆 1 2
𝑥1 = 𝑡
1 𝜆 + 2𝜆 − 5 5𝜆 + 𝜆 + 3 10 − 1 = 0
Question # 5
3𝜆 − 30𝜆 + 27 = 0
For what value 𝜆 the following
−27𝜆 + 27 = 0
system of homogenous equations
system.
𝜆=1
𝑥1 + 5𝑥2 + 3𝑥3 = 0
Now system becomes
5𝑥1 + 𝑥2 − 𝜆𝑥3 = 0
𝑥1 + 5𝑥2 + 3𝑥3 = 0 → (i)
𝑥1 + 2𝑥2 + 𝜆𝑥3 = 0
5𝑥1 + 𝑥2 − 𝑥3 = 0 → (ii)
Solution:
𝑥1 + 2𝑥2 + 𝑥3 = 0 → (iii)
Solving (i), (ii) 1
𝑥1 = 𝑥3 → 𝐵
3
1 5 3
10
𝑥1 =
3 3
𝑥 − 3𝑥3 Here A 5 1
1 2
10𝑥3 − 9𝑥3
=
3 It is given that the system has non-trivial
solution, so we put
𝑥3
𝑥1 = A 0
3
1 5 3 1 5 3 0
5 1 −𝜆 = 0
R2 ( 5 R1 )
1 2 𝜆 R 5 5 1 25 1 15 0
R ( R1 )
3
1 −𝜆 5 −𝜆 5 1 1 1 2 5 1 3 0
1 −5 +3 =0
2 𝜆 1 𝜆 1 2
1 5 3 0
1 𝜆 + 2𝜆 − 5 5𝜆 + 𝜆 + 3 10 − 1 = 0
R2 ( 5 R1 )
R 0 24 16 0
3𝜆 − 30𝜆 + 27 = 0 R ( R1 )
3
0 3 2 0
−27𝜆 + 27 = 0
1 5 3 0
−27𝜆 = −27
R 0 1 0
2 R2
3 24
𝜆=1 0 3 2 0
𝑥1 + 2𝑥2 + 𝑥3 = 0 1 5 3 0
R 0 1 0
2
Now for solution 3
0 0 0 0
1 5 3 0
From 𝑅2 , we have
R 5 1 1 0
1 2 1 0 2
0𝑥1 + 𝑥2 + 𝑥3 = 0
3
2 which is non-trivial solution.
⇒ 𝑥2 = − 𝑥3 → (𝐴)
3
From 𝑅1 , we have
2
𝑥1 + 5 − 𝑥3 + 3𝑥3 = 0
3
10
𝑥1 − 𝑥 + 3𝑥3 = 0
3 3
10
𝑥1 = 𝑥 − 3𝑥3
3 3
10𝑥3 − 9𝑥3
=
3
𝑥3
𝑥1 =
3
1
𝑥1 = 𝑥3 → 𝐵
3
Suppose 𝑥3 = 𝑡 then we have
1
𝑥1 = 𝑡
3
2
𝑥2 = − 𝑡
3